STRUKTUR DAN KEKAYAAN JENIS TUMBUHAN MANGROVE PASCA-TSUNAMI DI PULAU NIAS - Onrizal, Onrizal; Kusmana, Cecep (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Mangroves is an essential natural resources and vital component tor coastal areas both ecology and socio-economic.Adapted mangrove vegetation on tsunami disaster is important information for mangrove rehabilitation post-tsunami.The aim of the research was to determine the structure and species richness of mangrove vegetation post-tsunami in Aceh and Nias Island by vegetation analyses and inventory methods, field survey was carried out in March 2005 - three months after tsunami disaster.We found 20 adapted mangrove species post-tsunami in Nias island, dominated by Rhizophora apiculata. Land system of KJP was compound of 17 adapted mangrove species, and land system of PTG and KHY were each compound of 7 adapted mangrove species, Based on our research, we recommended that R. apiculaw is the first priority species to be used for mangrove rehabilitation in Nias island.